EFFECT OF TRAINING PROGRAMS ON TRAINEES’ LEARNING - Faisal-E-Alam, Md. (Bangladesh Journal of Multidisciplinary Scientific Research, 2024)
Employees’ learning is the primary driver of organizational sustainability. To achieve sustainability, organizations are required to invest in training for their employees’ continuous learning. Evaluation of training programs is the heart of continuous improvement in employees’ learning. This study investigates the effect of training programs on employees’ learning, focusing on knowledge-based outcomes (KBO), skill-based outcomes (SBO), and affective outcomes (AO). Drawing upon Human Capital Theory (HCT) and the second level of the Kirkpatrick's training evaluation model, a pre-experimental research design and quantitative method were employed. Stratified random sampling technique is used to select a sample of 381 employees from eight Private Commercial Banks (PCBs) of four bank generations in Bangladesh who participated in pre-test and post-test assessments. Statistical techniques including comparison chart, normality tests (Shapiro-Wilk W Test and Skewness and Kurtosis Test), and paired t-test were utilized to analyze the data. Findings indicate significant improvements in KBO, SBO, and AO following training interventions, supported by statistical test conducted using MS Excel v.13. Later, findings from executing STATA v.12 also underscore the effect of training programs on upgrading employees’ learning in the PCBs. Limitation includes the absence of a control group that hinders the influence of potential external factors on learning outcomes, which is a new avenue for future research. JEL Classification Codes: G21, M53, O15.